2022
DOI: 10.3390/biom12030417
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Malleability and Dysregulation in Cancer Progression: Understanding the Role of PARP1

Abstract: Mammalian genomic DNA methylation represents a key epigenetic modification and its dynamic regulation that fine-tunes the gene expression of multiple pathways during development. It maintains the gene expression of one generation of cells; particularly, the mitotic inheritance of gene-expression patterns makes it the key governing mechanism of epigenetic change to the next generation of cells. Convincing evidence from recent discoveries suggests that the dynamic regulation of DNA methylation is accomplished by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 273 publications
(258 reference statements)
0
5
0
Order By: Relevance
“…It is worth noting that both mRNA and protein expression of PARP1 was stimulated by estrogen in hUSLFs. PARP1 is a ubiquitous multifunctional nuclear enzyme that catalyzes the transfer of ADP-ribose units from NAD + to specific target proteins and controls important physiological processes such as DNA methylation, DNA damage response, chromatin remodeling and gene expression ( Srivastava and Lodhi, 2022 ) ( Swindall et al, 2013 ) ( Hassa and Hottiger, 2008 ). Several studies have proved that ERα could be poly(ADP-ribosyl)ated by binding to PARP1 and promoting ERα-dependent gene transcription ( Zhang et al, 2013 ; Gadad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that both mRNA and protein expression of PARP1 was stimulated by estrogen in hUSLFs. PARP1 is a ubiquitous multifunctional nuclear enzyme that catalyzes the transfer of ADP-ribose units from NAD + to specific target proteins and controls important physiological processes such as DNA methylation, DNA damage response, chromatin remodeling and gene expression ( Srivastava and Lodhi, 2022 ) ( Swindall et al, 2013 ) ( Hassa and Hottiger, 2008 ). Several studies have proved that ERα could be poly(ADP-ribosyl)ated by binding to PARP1 and promoting ERα-dependent gene transcription ( Zhang et al, 2013 ; Gadad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…(4) Estrogen/poly-ADP-ribose polymerase 1 PARP1 reverses mechanical transduction damage. PARP1 is a multifunctional nuclear enzyme that catalyzes the transfer of ADP-ribose units from NAD+ to specific target proteins, which controls important physiological processes such as DNA damage and gene expression ( 64 ). PARP1 is an important member of the antiapoptotic protein family.…”
Section: Impact Of Biomechanical-biochemical Coupling On Fibroblast F...mentioning
confidence: 99%
“…As the most extensively studied type of epigenetic modification necessary for the regulation of gene transcription, DNA methylation is a covalent modification of the nucleotide cytosine at the 5-position (164). Although it does not alter the DNA sequence, it has an important effect on gene expression and is often associated with gene silencing (165). A study has demonstrated that DNA hypomethylation may lead to the expression of PD-L1 and inhibitory cytokines, which can be immunosuppressive (166).…”
Section: Regulation Of Pd-l1 Expression In Solid Tumors By Dna Methyl...mentioning
confidence: 99%